Dead Sea Scrolls, revise and repeat: new methods and perspectives - Palmer, Carmen; Krause, Andrew R.; Schuller, Eileen M.; Screnock, John (Early Judaism and its literature, 2020)
Introduction: New Approaches to Old Questions / Andrew R. Krause, Carmen Palmer, and John Screnock -- Rule Texts from Qumran on the Spectrum of Jewish Legal Development / Sarianna Metso -- A Legal Approach to Textual Authority at Qumran: The Penal Codes as a Test Case / Jonathan Vroom -- Assessing the Character of Hebrew in the Dead Sea Scrolls: Historical Linguistics, Numerical Syntax, and the Notion of a Distinct "Dead Sea Scrolls" Hebrew / John Screnock -- Variant Readings in the Aramaic Dead Sea Scrolls: A Tool for Ongoing Research on the Textual Status and Linguistic Settings of Ancient Jewish Aramaic Literature / Andrew B. Perrin and Brandon Diggens -- Isaiah at Qumran and in the Gospel of Matthew / Kyung S. Baek -- The Threat of the Monstrous in the Scrolls / Heather Macumber -- Sectarian Identity an Angels Associated with Israel: A Comparison of Daniel 7-12 with 1QS, 11QMelchizedek, and 1QM / Matthew L. Walsh -- Function and Creativity in the Hebrew, Aramaic, and Cryptic Calendars from Qumran / Helen R. Jacobus -- Spirits of Controversy in My Bodily Structures: Spatiality of Body and Community in Qumran Apotropaic Prayers / Andrew R. Krause -- Sexuality and Self-Deprication in the Thanksgiving Psalms: Questions of Celibacy and the Presence of Women in the Yaḥad / Nicholas Meyer -- Masculinities and the Man of the Qumran Communities: Re-Evaluating the Ideals of Purification, Power, and Performance in the Dead Sea Scrolls / Jessica M. Keady -- Circumcision of the Heart in the Dead Sea Scrolls and in the Second Temple Period: Spiritual; Moral; and Ethnic / Carmen Palmer -- Experiencing the Solidity of Spaces in the Qumran Hodayot / Angela Kim Harkins.